Electrical engineering in context smart devices, robots & communications - Kuc, Roman (Cengage Learning, 2015)
Describes the basic components and technologies that make computer-assisted systems operate and cooperate, inviting the reader to understand by participating in the design process. This book starts with the basics and requires a working knowledge of algebra